Thermomechanical and morphological properties of sustainable mortars employing blast furnace slag and fly ash reinforced cement. Issue 1 (November 2020) - Farina, I; Singh, R; Singh, M; Preet, P; Kumar, R; Fraternali, F; Colangelo, F
Abstract: The blast furnace slag (BFS) is non-metallic co-product (such as silicates and alumina silicates etc.) which absorbs sulphur from the charge and comprises of around 20% (by weight) of Fe production and its use as reinforcement in cement mortar has been widely explored to improve thermal and compressive properties along with addressing the sustainability issues related to Fe production. But hitherto little has been reported on effect of BFS and fly ash (FA) reinforced cement mortar from surface topography, thermal stability and morphological properties view point. This paper reports the comparison of compressive, thermal and morphological properties of cement mortar with air cooled BFS and FA reinforced cement mortar as a case study. The results of study suggests that 80% of BFS and 20% FA reinforced cement mortar (cement: (BFS+FA): 1: (0.8+0.2) by weight%) possess lowest thermal conductivity (0.65W/mK), greatest porosity (29.65%) and acceptable compressive strength (6.6MPa) in comparison to cement mortar comprising of cement: sand as 1:1. The results are supported with compressive strength data, optical photo micrographs, thermal analysis based upon differential scanning calorimetry (DSC), surface topography (based upon 3D rendered images).